Silencing the phantom - pregabalin misuse in amputation patients: a case report - Danışman, Mustafa; Aşut, Gonca (Journal of Dependence, 2024)
In the aftermath of amputation, individuals face not only physical pain but also psychological challenges as their body's integrity is suddenly disrupted. Phantom limb sensations, characterized by the feeling that the amputated limb still exists, are common after amputation. Phantom limb pain often accompanies these sensations. Beyond the physiological aspects, patients' psychological adaptation journey is pivotal. This case report delves into the intricate relationship between phantom limb sensations, psychological factors, and pregabalin use disorder in a right-arm amputee patient. A 25-year-old right-arm amputee male patient went to an addiction outpatient clinic for pregabalin addiction treatment. He had a history of cannabis use to cope with his sadness during his adolescence. While cannabis use initially provided emotional relief, it later turned to pregabalin misuse, escalating to alarming doses (3000mg/day). Many pharmacological agents, including pregabalin, are being tried to treat phantom limb pain. Beyond its positive effects in phantom limb pain treatment, many studies have been published about its addictive features recently. This case underscores the need for comprehensive care for amputees, including psychological support, early prosthetic intervention, social reintegration, and judicious medication management. This case report serves as a reminder that the post-amputation period is not just a physical struggle but also a complex psychological journey toward healing and reintegration into a fulfilling life..
Keywords: Amputation; phantom limb pain; phantom limb syndrome; pregabalin; substance use disorder